Workforce in the regional economic development ecosystem (REDE): a case study of Tarrant County, Texas - Mercer, Eli Delane (Kansas State University, 2021)
This is a case study of Tarrant County, Texas, (TC) designed to shed light on workforce in the regional economic development ecosystem (REDE). The study was inspired by the Austin Technopolis Wheel and Model (Smilor, Gibson, & Kozmetsky, 1989; Gibson & Butler, 2013) and provides a practical look at the evolving REDE in Tarrant County, Texas, USA. The model is expanded to include the community college and teaching universities alongside research universities as additional categories of educational institution for study and analysis. Specific emphasis is placed on four areas of economic development including: Company Recruitment, Company Retention and Growth, Organic Growth (Startups/Entrepreneurship), and Collaborative Leadership Across Sectors. Fifty leaders and influencers from a variety of institutions and sectors involved in workforce and economic development activities in Tarrant County were interviewed. Analysis yielded insights into the current state of workforce and economic development as well as successes and failures in the region. This will help identify opportunities and gaps for Tarrant County leaders and influencers to enhance workforce and regional economic development as well as offer examples that other regions can consider and learn from as they navigate these challenges within their local context.
Keywords: Workforce; Economic development; Entrepreneurship; Regional economic development ecosystem (REDE); Collaborative leadership; Community leadership